Occurrence of Acaricidal Resistance on Ticks and Their Detection Measures - Chamuah, J. K.; Amenti; Lalchamliani (International Journal of Bio-resource and Stress Management, 2020)
Ectoparasites is one of the important cause for reduce growth and production of the animals. Among the ectoparasites, tick is the major causative agent for tick paralysis, tick injury, tick pyaemia along with transmission of different micro-organism to host animals. Acaricide resistance is a global phenomenon in all countries due to continuous and repeated use of acaricide in organized farms in years after year for long period of time. Predominance of resistance has been commonly observed in R. microplus in entire globes along with Indian subcontinent. However, occurrence of resistance against different hard tick, soft tick along with other ectoparasites has been documented in different form in different countries of the world. Acaricide resistance are initially present in very low proportion among ticks and would pass through next generation by reproduction of identical progeny. Resistance against acaricide acquired through target site modifications by mutation in the amino acid composition, increase in metabolic detoxification and excretion rate like esterase mediated point mutation is mainly responsible for occurrence of resistance in ticks and fly. Although use of Adult immersion test, Larval Packed test is the OIE recommended test for detection of acaricide resistance test. However molecular detection method is also quite convenient test for detection of acaricide resistance. In order to control this problem, change of medicated drugs, use of herbal drugs, and immunoprophylaxis along with management procedure may control this problem in today’s context.